A study on students failure in completing Diploma in Accountancy program within the stipulated time frame. A case study: DIA students at UiTM Alor Gajah Melaka / Azizah Dollah … [et al.] - Dollah, Azizah; Bani, Hamidah; Sapari, Afidah; Abdul Manan, Nor Suhailati (Faculty of Accountancy, 2001)
The issue of failures among DIA students at UiTM Melaka Branch is explored. This study presents factors contributing to the failures. The result of the study shows that punctuality, goal commitment and social and psychological issues are factors that contribute to DIA students9 failure to complete their study within stipulated time. It is also found that there is significant difference between the failures and the graduates on factors such as goal commitment and social and psychological issue. DIA students UiTM Melaka Branch from two different groups that is the failures and the graduates are used as sample to test the hypothesis. Structured questionnaires were distributed to 99 students during class hour. The result of this study was supported by Garba&Aldosary(99), Tinto(75) and W. Astin(64)